OPPOSITION TO RAIDING AS PART OF STATE ECONOMIC SECURITY POLICY - Меlnychenko O.A.; Pushkariova V.I. (Pressing Problems of Public Administration, 2015)
An overview of causes and consequences of raiding has been made. The essence of theconcepts of ‘raiding’ and ‘opposition to raiding’ is specified. The classification of raidingcounteraction components has been upgraded. Priority areas of implementing the state policy ofeconomic security in the sphere are highlighted.